Solutions to Enhance Corporate Sales Performance in Vietnam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article presents some solutions to improve sales performance in private enterprisesin Ho Chi Minh City (Vietnam) in line with the trend of globalization and international economicintegration. The article has thoroughly analyzed the theoretical basis of the sales concepts, the roleof the sales in business, the and the sales management process and the related practices of thoseissues in Vietnam.